2022
DOI: 10.34233/jpr.1205727
|View full text |Cite
|
Sign up to set email alerts
|

Broiler Chickens' Growth, Haematological Indices, Guts Microbiota, Carcass and Meat Analysis in Response to Dietary Supplementation with Anacardium occidentale Leaf Powder and A Mix of Prebiotic, Probiotic and Acidifier

Abstract: This 42-day study evaluates the broiler chickens' response to dietary supplementation with Anacardium occidentale leaf powder (ALP) and a mix of prebiotic, probiotic and acidifier (PPA). Two baseline diets were compounded for the starter phase (age 1-21 days) and finisher phase (age 22-42 days) and divided into four parts: Diet 1(control), Diet 2 (250mg/kg PPA), Diet 3 (2,500mg/kg ALP), and Diet 4 (250mg/kg PPA+2,500mg/kg ALP). 240 Cobb 500 broiler chicks were distributed randomly to the experimental diets (6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The concentrations of RBC and Hb in all treatment groups were still within the acceptable ranges for normal chickens. The range of normal hematological values of RBC and Hb for broilers was 2.5–3.5 × 10 6 /μl and 10.20 gm/dl, respectively, as supported by El-Latif et al [ 26 ] and Oloruntola et al [ 27 ]. The slightly improved RBC count and Hb concentration of birds fed DoLa in this study suggest the supplements under study enhanced the adequate ingestion and absorption of essential nutrients that are needed in the processes involved in erythropoiesis.…”
Section: Discussionsupporting
confidence: 56%
“…The concentrations of RBC and Hb in all treatment groups were still within the acceptable ranges for normal chickens. The range of normal hematological values of RBC and Hb for broilers was 2.5–3.5 × 10 6 /μl and 10.20 gm/dl, respectively, as supported by El-Latif et al [ 26 ] and Oloruntola et al [ 27 ]. The slightly improved RBC count and Hb concentration of birds fed DoLa in this study suggest the supplements under study enhanced the adequate ingestion and absorption of essential nutrients that are needed in the processes involved in erythropoiesis.…”
Section: Discussionsupporting
confidence: 56%
“…The value obtained for red blood cell also suggests that the supply of oxygen from the lungs to different blood tissues was not compromised which gives room for efficient nutrient distribution in the body of birds (Alagbe, 2024a(Alagbe, , 2024b. Oloruntola et al (2022) reported that dietary supplementation of Anacardium occidentale leaf powder improved red blood cell, pack cell volume and haemoglobin values than those given antibiotics. White blood cell values in starter and finisher phase within the normal range [8.00-14.00 (×109/L)] and [9.50-21.0 (×109/L)] reported by Meluzzi et al (1992) and Nanbol et al (2016).…”
Section: Discussionmentioning
confidence: 99%